Apunirereha und Ria, Salomonen Inseln. Vorgeschichte der Salomonen Inseln. Die Arbeiten der Jahre 2015 bis 2017 - Moser, Johannes (e-Forschungsberichte des DAI, 2018)
Within the research project “Prehistory of the Solomon Islands” archaeological investigations have been conducted continuously at the flint knapping atelier Apunirereha and under the Ria-Rockshelter in the province of East Are Are on the island of Malaita. Apunirereha is an open air site and shows different zones of individual activities based on the sorting and spatial distribution of the lithic tools. Radiocarbon dates indicating a long sequence of habitation and activities at the site. The rock overhang Ria shows evidence of human presence in prehistoric times. The excavations under the shelter disclosed cultural deposits and features as well as a large collection of knapped stone tools, shells and faunal remains. In the shelter’s rear two extended supine burials and remains of an infant were discovered under a pebble pavement. During the excavation in 2017 remains of a fourth individual came to light.